Peran Guru Mengaji Dalam Meningkatkan Kemampuan Baca Tulis Al Qur’an Pada Santri TPA Asy Syakur Paron Ngawi - Dian Febrianingsih; Joko Purnomo (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study was to find out 1) Description of the ability to read and write the Koran in Santri TPA Asy Syakur Paron Ngawi, 2) What are the obstacles to the role of the Koran Teacher in Improving the Ability to Read and Write the Qur'an in Santri TPA Asy Syakur Paron Ngawi. In this study, researchers used descriptive qualitative research methods. Qualitative descriptive research is explaining things as they are so as to provide a clear picture according to field situations as they are. The research approach can be briefly distinguished into several types, depending on the point of view, although in fact one type overlaps with another. According to the researcher, this descriptive research approach is a type of research to describe all research findings in detail and according to existing situations. The subjects in this study were students, TPA teachers, guardians of TPA Asy Syakur Paron Ngawi students. In this case the researcher chose the subject of 3 student guardians with the criteria of having a good educational background and experience in religious matters. And for the reasons for selecting 5 students out of 72 students, namely having good morals, being disciplined and being able to be trusted for information retrieval. Data collection techniques carried out through observation, interviews and documentation. The results of this study are the role of the Koran teacher in improving the ability to read and write the Koran to students at TPA Asy Syakur Paron Ngawi by: 1) Motivating students by giving advice, guidance so that students are encouraged to want to read Al -Qur'an in daily life, 2) Approach individually to students who are unable and experience difficulties in learning to read and write Al-Qur'an, 3) Application of effective methods The obstacles to the teacher reciting the Koran in improving the reading and writing ability of the Qur'an for students at TPA Asy Syakur Paron Ngawi are: 1) lack of motivation and attention from parents and an unsupportive environment, 2) lack of awareness of students about the importance of learning to read and write Al-Qur'an, 3) Lack of interest in children to learn to read and write Al-Qur'an.